2011
DOI: 10.1136/bjophthalmol-2011-300354
|View full text |Cite
|
Sign up to set email alerts
|

Detection of retinal nerve fibre layer progression: comparison of the fast and extended modes of GDx guided progression analysis

Abstract: Purpose To compare detection of retinal nerve fiber layer (RNFL) changes using GDx Guided Progression Analysis (GPA) fast mode (which assumes fixed variability of a reference population) and extended mode (which measures individual variability) and to determine how they compare to photography and visual field based conventional methods for identifying glaucoma progression. Methods 172 eyes from 117 participants in the Diagnostic Innovations in Glaucoma Study (DIGS) (12 healthy, 108 glaucoma suspect and 52 gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 27 publications
2
4
0
Order By: Relevance
“…Most of the remaining five eyes that demonstrated VF progression without corresponding GDx GPA progression had advanced structural damage that might indicate that the structural changes precede the functional changes or that functional assessment is more sensitive to detect changes in advanced stages of glaucoma. These results agree with previous studies reporting limited agreement between structural and functional progression detection methods 2 10 15–17. In a study by Alencar et al ,9 the GDx GPA was only able to identify 50% of the eyes that were detected as progressing by VF and stereophotographs.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Most of the remaining five eyes that demonstrated VF progression without corresponding GDx GPA progression had advanced structural damage that might indicate that the structural changes precede the functional changes or that functional assessment is more sensitive to detect changes in advanced stages of glaucoma. These results agree with previous studies reporting limited agreement between structural and functional progression detection methods 2 10 15–17. In a study by Alencar et al ,9 the GDx GPA was only able to identify 50% of the eyes that were detected as progressing by VF and stereophotographs.…”
Section: Discussionsupporting
confidence: 93%
“…Similar to a previous study, we observed poor agreement between VF and GDx GPA regardless of the use of population- or individual-derived variability criteria 10. However, RNFL thickness slope was significantly different between VF defined progressors and non-progressors.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…76 The results of Fast Mode are more variable than Extended Mode, depending on which two scans are included in the baseline and follow-up images. 77 When judging structural change using GDx-GPA, it is important to understand the GPA printout and use in conjunction with clinical judgment for final decision.…”
Section: Monitoring Glaucoma Progressionmentioning
confidence: 99%
“…However, in most studies that assess the inter-instrument agreement on progression detection on proprietary change detection algorithms, this agreement is moderate at best 15. This holds true even for progression detection algorithms that operate on data from the same instrument, whether this is functional16 17 or structural data 18 19. The latter is further explored for GDx guided progression analysis in the paper by Folio et al ,20 elsewhere in this issue, where the authors evaluate progression detection based on population-derived reproducibilities (guided progression analysis fast mode) versus individual-derived reproducibilities (guided progression analysis extended mode).…”
Section: Methods Available For Clinical Usementioning
confidence: 99%